Non-Operative Management of Liver Trauma. Issue 2 (1st June 2012) - Swift, C; Garner, Jeff
Abstract : The liver is one of the commonest intra-abdominal organs injured worldwide in blunt and penetrating trauma and its management has evolved significantly in the last 30 years. Mandatory laparotomy has been replaced by an acceptance that for most blunt hepatic trauma, a selective non-operative approach is safe and effective with a failure rate ie the need to proceed to delayed laparotomy of approximately 10%. There is a markedly lower rate of complications in those that are managed non-operatively. Adjuncts to this conservative regimen such as angioembolisation and delayed laparoscopy to treat biliary peritonitis increase the chances of avoiding laparotomy. This belief in non-operative management has also been transferred to some degree to penetrating liver trauma, where there is a gradual accumulation of evidence to support this non-operative approach in a carefully selected group of patients. This article examines the evidence supporting the selective non-operative management of both blunt and penetrating liver trauma and describes the outcomes and complications.